The role of hemoglobin degradation pathway in preeclampsia: A systematic review and meta-analysis. (March 2020) - Bellos, Ioannis; Pergialiotis, Vasilios; Loutradis, Dimitrios; Papapanagiotou, Angeliki; Daskalakis, Georgios
Abstract: Introduction: Overproduction of fetal hemoglobin by the placenta leading to increased consumption of endogenous heme scavenging proteins has been recently implicated as a novel pathway in the pathogenesis of preeclampsia. The aim of the present systematic review was to evaluate maternal serum levels of fetal hemoglobin, haptoglobin, heme oxygenase-1, hemopexin and α1-microglobulin, as well as haptoglobin phenotypes among preeclamptic and healthy pregnant women and assess their predictive role in the disease. Methods: Medline, Scopus, CENTRAL, Clinicaltrials.gov and Google Scholar databases were systematically searched from inception. All studies comparing levels of fetal hemoglobin or heme scavengers among preeclamptic and healthy pregnant controls were deemed eligible. Results: Twenty-three studies were included, with a total number of 7461 pregnant women. Quantitative synthesis was not conducted for the comparison of serum levels due to high heterogeneity. Current evidence suggests that preeclampsia is associated with increased levels of fetal hemoglobin and α1-microglobulin, as well as with lower levels of serum hemopexin. Data regarding serum haptoglobin and heme oxygenase-1 were conflicting, as the available evidence did not unanimously suggest a significant change of their levels in the disease. Network meta-analysis indicated no significant association for any of the haptoglobin phenotypes with preeclampsia development. Discussion: The present review suggests that preeclampsia may be associated with increased fetal hemoglobin and α1-microglobulin and decreased hemopexin levels, although inter-study heterogeneity was high. Future large-scale studies are needed to fully elucidate the predictive efficacy of these markers by introducing cut-off values and defining the optimal gestational age for sampling. Highlights: Preeclampsia is linked to higher HbF, α1-microglobulin and lower hemopexin levels. Haptoglobin phenotype does not alter preeclampsia risk. Future cohort studies should define the optimum cut-offs to be widely used. The most appropriate gestational age for sampling remains to be elucidated.